(untitled) (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
Thin-walled shell structure may achieve such innovative structure enhancing better aesthetic view which should lead better performance in aspect of structural response; conducting accurate optimistic analysis and design for geo-strata of Earth or space objects. Nowadays, in developing countries for design of Stupa, Gumbaz and several dome structure simple spherical, parabolic three-dimensional structures are being rapidly analyzed and designed without proper analysis in which continuity of elastic theory enhancing member and bending forces developed within such structure should be considered. In this paper it is explained how the peak stress in intersecting line of several complex shell structures are being normalized and the continuity of elastic theory is maintained even though the structures are to be used in space purpose and will be constructed on the geo-strata of Lunar and Planetary objects. Those shell structures are not only in simple type like conventional dome structures; but also, innovative shell structures like Mongue’s surfaces, Barrel Vaults, folded plate structures may be selected for space to resist pressure difference of internal and external environment in space, moon or any planet creating complex and aesthetic performance by humankind. Thin-walled spatial structures used in various fields of technology are often combinations of sectors of thin shells and plates which may be connected at edge zones or may be intersected to each other along common intersecting line which will form its own continuity function. During analyze of various responses of connected structures, it is necessary to take into account the joint work of the sections of the structure, especially in the zone of intersection of the sections. At the same time, both two sectors or more than two sectors of thin shell may intersect in the intersection zone for covering large space consisting only peripheral stiff columns within shell structures. Intersecting sectors may be either of the same geometric shape or different depends upon designer in aesthetic sense, environment of space vacuum and geo-strata of space objects. The article provides study of innovative thin shell structure used in space which is found rarely explained worldwide. An approach for analyzing connected or intersected thin shell structures based on the variation-difference method and the super element method is considered either using force or stiffness method to obtain optimization of structural parameters. The main aim of this paper is to focus on to conduct analysis of shell structure for Lunar surfaces or surfaces of other planetary objects which may resist extreme temperature, cosmic radiation and pressure difference. The boundary conditions for such shell structure are introduced as zero gravity, spring elements and assigned restrained in periphery of the shell must be matching with real features. This paper also motivates the structural engineers to develop innovative design of buildings, bridges and other monuments for future generations conducting construction of such shell structure in Earth and space as well.